Estratégias de sustentabilidade para um ecoturismo na zona costeira maranhense, município de Paço do Lumiar - JESUS, Dione Milena Moraes de (2024)
The dissertation aims to present sustainable development strategies for the practice of ecotourism in the municipality of Paço do Lumiar, considering the complex relationship of the tourism system, which is characterized by its interdisciplinary nature from the perspective of the environment-society relationship. It presents the relationship between ecotourism and environmental education from the perspective of landscape geoecology, highlighting the importance of understanding the natural environment to plan all aspects of tourism, consideringthe destination's characteristics and the influence of the activity on the educational process.Additionally, it examines mapping from the perspective of landscape characteristics with the aim of understanding the environment to minimize the negative impacts of tourist activities.The dissertation also includes a description of the tourism potentials and the trade's perception of ecotourism through interviews and direct observation, supported by theoretical and documentary references. Considering that the activity is still quite modest, it is possible to plan the carrying capacity of attractions, the implementation of public policies aimed at promoting the destination, which can boost the local economy by generating employment and income, as well as use the information to contribute to the appreciation and understanding of environmental heritage value through projects in the public education network and the creation of a Tourist Information Center to disseminate reliable information, alongside promoting handicraft sales and tour itineraries in the same space.